2020
DOI: 10.3390/met10040531
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Lead and Zinc from Zinc Plant Leach Residues by Concurrent Dissolution-Cementation Using Zero-Valent Aluminum in Chloride Medium

Abstract: Zinc plant leach residues (ZPLRs) contain significant amounts of metal compounds of lead (Pb), zinc (Zn), iron (Fe), etc., hence, they are considered as a secondary source of metals. On the other hand, ZPLRs are regarded as hazardous materials because they contain heavy metals that pollute the environment. Resources and environmental concerns of ZPLRs were addressed in this study by removing/recovering Pb and Zn using a concurrent dissolution and cementation technique. To cement the dissolved Pb and Zn in leac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…These results suggest that most of the toxic and hazardous elements detected by XRF are likely hosted by sulfide minerals in the MT sample. Even in minor to trace amounts, sulfide minerals play crucial roles in the mobility of environmentally regulated elements like As, Cd, Cu and Zn as noted by several authors ( Kamata and Katoh, 2019 ; Mar et al., 2013 ; Silwamba et al., 2020a , b ; Tabelin et al., 2010 , 2012d ; 2014b ; 2017b ). Kamata and Katoh (2019) , for example, reported that the release of As and heavy metals like Cu, Zn and Pb from marine sedimentary rocks is strongly influenced by the oxidation of sulfide minerals and the subsequent precipitation of iron-oxyhydroxides.…”
Section: Resultsmentioning
confidence: 94%
“…These results suggest that most of the toxic and hazardous elements detected by XRF are likely hosted by sulfide minerals in the MT sample. Even in minor to trace amounts, sulfide minerals play crucial roles in the mobility of environmentally regulated elements like As, Cd, Cu and Zn as noted by several authors ( Kamata and Katoh, 2019 ; Mar et al., 2013 ; Silwamba et al., 2020a , b ; Tabelin et al., 2010 , 2012d ; 2014b ; 2017b ). Kamata and Katoh (2019) , for example, reported that the release of As and heavy metals like Cu, Zn and Pb from marine sedimentary rocks is strongly influenced by the oxidation of sulfide minerals and the subsequent precipitation of iron-oxyhydroxides.…”
Section: Resultsmentioning
confidence: 94%
“…Above pH 7.5 to alkaline conditions, there was production of hydroxyl groups and consequently increased the amount of lead hydroxide solution [67,68]. Silwamba et al, [69] have also showed that the addition of hydrochloric acid can form Pb 2+ and lead chloride complexes such as PbCl + , PbCl 2 , and PbCl 3 -. The reason why Pb(II) ions were adsorbed more than Cr(VI) ions on PNS and FNS composites might be due to negatively charged Cr(VI) ion electrostatically repelling the adsorbed ions resulting in a decrease of the adsorption capacity.…”
Section: Speciationmentioning
confidence: 98%
“…The mobility of heavy metals in contaminated soils, rocks and sediments is typically determined by the balance between release and retention mechanisms under a given geochemical condition ( Marove et al., 2020 ; Silwamba et al., 2020 ; Tabelin et al., 2018 ). On one hand, sulphide oxidation is likely the most dominant release mechanism of Cu, Pb and Zn from the ASGM-impacted soils because under oxidising and slightly alkaline (pH 8.2–8.7) conditions, HFOs and carbonates are more stable than sulphide minerals.…”
Section: Resultsmentioning
confidence: 99%